Effectiveness, Challenges and Countermeasures of China-CEE Cooperation - Zhu, Qianyu; Yan, Xiaoshan (Archives of Business Research, 2020)
China-Central and Eastern European Cooperation (referred to as “16+1”, later developed into “17+1” or China-CEE Cooperation) is an important element and effective complement to China's efforts to promote the development of cooperation among the 17 CEE countries, the balanced development of the CEE sub-regional and the development of various areas of China-EU cooperation. Since 2012, when the framework was proposed, it has witnessed the establishment of a cooperation and coordination mechanism guided by leaders' meetings, ministerial meetings and forums or expositions for building a comprehensive, multi-field and multi-level pattern of cooperation. The framework is based on the interests of both sides and in line with the trend of common development, mutual benefit and win-win. In the eight years, it has achieved fruitful results in the areas of policy communication, trade and investment growth, infrastructure construction, capital financing and civil exchanges, so as to promote the economic stability and sustainable development of countries involved. It also faces internal and external challenges, like the imbalanced development, divergent interests, interference by interested countries, and the deterioration of security situation in the Middle East. As the cooperation deepens, it is important to adhere to the principles of mutual benefit and win-win and dock with different frameworks on all fronts. It is necessary to better understand EU laws and regulations and seize new opportunities for cooperation, including civil exchanges, etc.